Poly (3‐hydroxybutyrate)/cellulose nanocrystal films for food packaging applications: Barrier and migration studies. Issue 10 (12th June 2015) - Dhar, Prodyut; Bhardwaj, Umesh; Kumar, Amit; Katiyar, Vimal
<x xml:space="preserve">Abstract</x> This article reports the fabrication of poly (3‐hydroxybutyrate) (PHB)/cellulose nanocrystal (CNC) based nanobiocomposite films with improved gas barrier and migration properties for food packaging applications. Acid hydrolysis of cellulose pulp from bamboo (Bambusabalcooa) yields CNCs with diameter of 15–20 nm and length of 400–600 nm. Evaluation of d‐spacing using XRD indicates intercalation of PHB matrix with CNC at optimum loadings of 2 wt%. Overall migration values in presence of both polar and nonpolar food simulants are found within standard limits. After migration studies on PHB/CNC films, significant decrease in crystallization temperature (by 15°C) is observed, with subsequent presence of multiple melting peaks. The oxygen transmission rate (OTR) decreases significantly (by ∼65%), even at low CNC (∼2 wt%) loadings. Permeation activation energy (calculated from Arrhenius equation) and barrier properties, such as solubility and diffusivity, improved (decreased by ∼57 and 17%, respectively) with loading fractions (∼2 wt%) due to the hydrogen bonded interaction of PHB with CNCs as well as tortuous path provided towards oxygen permeation. POLYM. ENG. SCI., 55:2388–2395, 2015. © 2015 Society of Plastics Engineers